Is salvage surgery for patients with lung cancer after carbon ion radiotherapy easy or difficult?. (16th January 2019) - Ohtaki, Yoichi; Shimizu, Kimihiro; Saitoh, Jun-Ichi; Kamiyoshihara, Mitsuhiro; Mogi, Akira; Nakazawa, Seshiru; Ohno, Tatsuya; Shirabe, Ken
Abstract: Carbon ion radiotherapy (CIRT) shows higher local control rates and minimal damage to normal lung parenchyma compared with conventional radiotherapy; however, some patients experience local recurrence. The efficacy and safety of salvage surgery after CIRT for non-small-cell lung cancer are unclear. We reviewed clinical, surgical, pathological and prognostic data of 6 patients who underwent salvage surgery after CIRT between 2010 and 2015. All patients were men with a smoking history, and their median age was 67 years. The time from CIRT to surgery was 18 (range 12–24) months. All patients underwent at least lobectomy with mediastinal node dissection. Viable tumour cells were confirmed pathologically in all cases. Five patients required combined resection or extra procedure because of strong adhesions and the possibility of tumour extension; however, none of the patients had a tumour invasion to the adjacent organ. None of the patients had severe complications, perioperative death and local recurrence, and 3 patients are alive without recurrence (range 28–84 months). Salvage surgery appears to be safe and effective. Even though the tumours did not invade the adjacent organs, combined resection was required because of severe adhesion.